2013
DOI: 10.1673/031.013.4101
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Precision Sequential Sampling Plans for Estimating Alfalfa Caterpillar,Colias lesbia, Egg Density in Alfalfa,Medicago sativa, Fields in Córdoba, Argentina

Abstract: The alfalfa caterpillar, Colias lesbia (Fabricius) (Lepidoptera: Pieridae), is a major pest of alfalfa, Medicago sativa L. (Fabales: Fabaceae), crops in Argentina. Its management is based mainly on chemical control of larvae whenever the larvae exceed the action threshold. To develop and validate fixed-precision sequential sampling plans, an intensive sampling programme for C. lesbia eggs was carried out in two alfalfa plots located in the Province of Córdoba, Argentina, from 1999 to 2002. Using Resampling for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…(Lepidoptera: Pieridae). Se trata de la principal plaga de la alfalfa (Serra et al, 2013), leguminosa cultivada en el predio donde realizamos la plantación. El tala fue levemente más afectado, posiblemente a causa de mayor área foliar efectiva con respecto al algarrobo (tala 409.6 mm 2 vs algarrobo 25.2 mm 2 ) (Zeballos et al, 2014).…”
Section: Discussionunclassified
“…(Lepidoptera: Pieridae). Se trata de la principal plaga de la alfalfa (Serra et al, 2013), leguminosa cultivada en el predio donde realizamos la plantación. El tala fue levemente más afectado, posiblemente a causa de mayor área foliar efectiva con respecto al algarrobo (tala 409.6 mm 2 vs algarrobo 25.2 mm 2 ) (Zeballos et al, 2014).…”
Section: Discussionunclassified
“…where T n is the critical cumulative count over n samples (number of larvae or damaged fruit), a and b are the estimated parameters in model (1a), and D is the desired level of precision (Serra et al, 2013). Kuno's (1969) fi xed-precision sampling algorithm uses the parameters of Iwao's patchiness model (2) based on Lloyd's mean crowding index m*.…”
Section: Minimum Number Of Samples and Plans For Fi Xed Precision Seqmentioning
confidence: 99%
“…In order to ensure that T n remains positive in Kuno's plan n > (b -1) / D 2 (Naranjo & Hutchison, 1997). In population dynamics studies, a precision level of 0.10 is usually suggested (Southwood, 1978), while for decision making in pest management a precision level of 0.20 or 0.25 is preferred (Serra et al, 2013). In the current survey, three precision levels D = 0.10, 0.15 or 0.20 were chosen to develop plans for sampling that cover most circumstances.…”
Section: Minimum Number Of Samples and Plans For Fi Xed Precision Seqmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedigo (1993) emphasized that the absence of cost-effective, user-friendly sampling plans for arthropod pests in food crops is a major impediment to the adoption of IPM. Several studies have demonstrated that deployment of reliable and practically feasible sampling plans may lead to reduction in pesticide applications and improved pest management (Sylvester and Cox 1961, Giles et al 2000, Butler and Trumble 2012, Martini et al 2012, Serra et al 2013, Stubbins et al 2014. Within a sampling plan, the sampling technique, unit, and pattern must be defined, and the accuracy and efficiency must be addressed, which are often competing needs (Landis 1993, Pedigo 1993.…”
mentioning
confidence: 99%